Disciplinary convergence: landscape architecture and the spatial design disciplines. Issue 1 (2nd January 2016) - Kullmann, Karl
Abstract: Despite resurgent interest in landscape, the viability of landscape architecture has been questioned from within the field. The article positions this uncertainty as a symptom of shifts among the spatial design disciplines, which are enmeshed in a process of appropriation, relinquishment, and overlap of territory. Whereas the convergence of the spatial design disciplines has been interpreted as emblematic of landscape-based trans-disciplinary practice, a more contested cross-disciplinary interaction is identified and explored through analysis of design competition prizes and professional magazines. The discussion focusses on the interactions between architecture and landscape architecture, and considers potential implications for education and practice.